Mcm10 promotes rapid isomerization of CMG-DNA for replisome bypass of lagging strand DNA blocks - Langston, Lance D (eLife, 2017)
Replicative helicases in all cell types are hexameric rings that unwind DNA by steric exclusion in which the helicase encircles the tracking strand only and excludes the other strand from the ring. This mode of translocation allows helicases to bypass blocks on the strand that is excluded from the central channel. Unlike other replicative helicases, eukaryotic CMG helicase partially encircles duplex DNA at a forked junction and is stopped by a block on the non-tracking (lagging) strand. This report demonstrates that Mcm10, an essential replication protein unique to eukaryotes, binds CMG and greatly stimulates its helicase activity in vitro. Most significantly, Mcm10 enables CMG and the replisome to bypass blocks on the non-tracking DNA strand. We demonstrate that bypass occurs without displacement of the blocks and therefore Mcm10 must isomerize the CMG-DNA complex to achieve the bypass function.